Eksistensi Polluter Pays Principle dalam Pengaturan Hukum Lingkungan di Indonesia - Muhamad Muhdar (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2009)
Polluter- Pays Principle (PPP) was initially known as economic instrument to maintain the balance between natural resources exploitation and economic activities. In its further development, PPP was defined as basic instrument of legal responsibility. In Indonesian legal perspective, PPP was not arranged adequately, either in its basic level of law arrangement or in its definition subsisted in court’s verdicts, including its clear existence in legal system. However, the principle has become reference in practical level, especially in the settlement of environmental pollution cases. For Indonesia, the position of this principle was supposed to be defined in accordance with its purposes of formulation by applying economic instruments, such as charge for guarantee fund, environmental tax, as well as charge for environmental service. In legal perspective, the principle was not relevant to be used as the basis for legal responsibility, including cannot be understood as an excuse for polluting.